Investigação do polimorfismo rs7903146 no gene TCF7L2 como biomarcador de transtorno neurocognitivo - Aguiar, Paola Sossai (2021)
The TCF7L2 gene, associated with hyperglycemia, hyperinsulinemia and, more recently, decreased volume of brain regions, participates in the Wnt pathway, a set of conserved and widely expressed transduction pathways throughout the body. Important for glucose homeostasis and for functions of growth, metabolism and cell survival, this pathway has great impact on the development and maintenance of adequate neuronal function in the human brain. Recent evidence points to a shared genetic architecture between metabolic alterations, the Diabetes Mellitus (DM) Type 3 theory, and Neurocognitive Disorder (NCD) involving the TCF7L2 locus. Cerebral hyperinsulinemia related to dysregulation on signaling pathways, mainly the Wnt pathway, could accelerate the deposition of abnormal proteins in the brain and decrease brain glucose metabolismo. The hypothesis under investigation is that the rs7903146 polymorphism in TCF7L2, the strongest GWAS signal for Type 2 DM, is associated with development of NCD. Participants in the study "Health, well-being and aging", with complete data on age, gender, DM and stroke (N=1118), were classified for NCD using the score obtained in the Mini Mental State Examination ( MMSE). Participants who scored below the MMSE cutoff line (13) were considered to have NCD (N=144). NCD was 1.62 times more likely to occur in homozygotes for the C allele compared to carriers of other genotypes (χ2 = 7.189; P = 0.007; OR 1.62 95% CI 1.14 – 2.30). Among those aged 80 years and over, carriers homozygous for C scored a mean of 2 points lower on MMSE (P = 0.003). In addition to NCD, the C allele was also associated with obesity (χ2 = 7.198; P = 0.007; OR 1.43 95% CI 1.101–1.868 RR 1.282 95% CI 1.069–1.537) and increased waist circumference (χ2 = 4.346 ; P = 0.037; OR 1.296 95% CI 1.02-1.66; RR 1.13 95% CI 1.01-1.27). On the other hand, the T allele in homozygosis was shown to be a risk for hyperglycemia (χ2 = 4.874; P = 0.027; OR 1.59 95% CI 1.05–2.41; RR 1.04 95% CI 1.01- 1.08), DM (χ2 = 7.00; P = 0.008; OR 1.8 95% CI 1.20–2.80; RR 1.50 95% CI 1.10–2.00), and also for stroke (χ2 = 7.143; P = 0.008; OR 2.22 95% CI 1.22–4.03; RR 1.10 95% CI 1.01-1.21). DM was not associated with NCD risk. The results found support the hypothesis that the NCD have a complex genetic architecture shared with metabolic traits.